2006
DOI: 10.1002/jbm.a.30722
|View full text |Cite
|
Sign up to set email alerts
|

Significantly accelerated osteoblast cell growth on aligned TiO2 nanotubes

Abstract: Vertically aligned yet laterally spaced nanoscale TiO2 nanotubes have been grown on Ti by anodization, and the growth of MC3T3-E1 osteoblast cells on such nanotubes has been investigated. The adhesion/propagation of the osteoblast is substantially improved by the topography of the TiO2 nanotubes with the filopodia of growing cells actually going into the nanotube pores, producing an interlocked cell structure. The presence of the nanotube structure induced a significant acceleration in the growth rate of osteo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

20
341
6
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 451 publications
(392 citation statements)
references
References 28 publications
20
341
6
1
Order By: Relevance
“…We also demonstrate that a guided osteogenic differentiation of hMSCs can be controllably manipulated by selective sizing of the nanotube dimensions. Because the TiO 2 nanotubes are excellent osseointegration biomaterials as evidenced by in vitro data (24), and our preliminary in vivo animal data indicating a strong new bone integration on the nanotube surface with reduced soft tissue trapping (data not shown), the nanotube surface can perform dual therapeutic functions of specifically guided differentiation and strong osseointegration for new bone formation. We forecast that these results can be a milestone for the further study of stem cell control and implant development, in terms of its application as a therapeutic platform as well.…”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations
“…We also demonstrate that a guided osteogenic differentiation of hMSCs can be controllably manipulated by selective sizing of the nanotube dimensions. Because the TiO 2 nanotubes are excellent osseointegration biomaterials as evidenced by in vitro data (24), and our preliminary in vivo animal data indicating a strong new bone integration on the nanotube surface with reduced soft tissue trapping (data not shown), the nanotube surface can perform dual therapeutic functions of specifically guided differentiation and strong osseointegration for new bone formation. We forecast that these results can be a milestone for the further study of stem cell control and implant development, in terms of its application as a therapeutic platform as well.…”
Section: Discussionmentioning
confidence: 86%
“…We have described in previous studies (24) that the long-range structure of TiO 2 nanotubes is neither patterned nor highly ordered, but they do have a robust and discrete nanotube shape. Dalby et al (7) reported that MSC cultured on highly ordered poly(methylmethacrylate) (PMMA) nanopatterns showed negligible osteogenic differentiation, but randomized PMMA nanotopography demonstrated MSC osteoblastic morphologies after 21 days of incubation with cell growth media.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Third, there are differences in the nature of the TiO 2 nanotubes used. The nanotubes used by Park et al were as-anodized amorphous phase, whereas those used in our study were heat treated and crystallized, anatase phase; we have previously demonstrated that crystallized TiO 2 nanotubes are superior in osteoblast cell adhesion and growth (5,6) and that the anatase phase plays an important role in proliferation and cell morphology. Furthermore, Park et al's (2, 3) amorphous nanotube samples can exhibit 5% fluorine at the sample surface (3), whereas our sample (4) surface was high-temperature annealed at 500°C to thermally decompose and remove most of the fluorine (XPS showing only 0.4%).…”
mentioning
confidence: 87%